Full 360° Terahertz Dynamic Phase Modulation Based on Doubly Resonant Graphene–Metal Hybrid Metasurfaces - Binxu Wang (MDPI AG, 2021)
Dynamic phase modulation is vital for tuneable focusing, beaming, polarisation conversion and holography. However, it remains challenging to achieve full 360° dynamic phase modulation while maintaining high reflectance or transmittance based on metamaterials or metasurfaces in the terahertz regime. Here, we propose a doubly resonant graphene–metal hybrid metasurface to address this challenge. Simulation results show that by varying the graphene Fermi energy, the proposed metasurface with two shifting resonances is capable of providing dynamic phase modulation covering a range of 361° while maintaining relatively high reflectance above 20% at 1.05 THz. Based on the phase profile design, dynamically tuneable beam steering and focusing were numerically demonstrated. We expect that this work will advance the engineering of graphene metasurfaces for the dynamic manipulation of terahertz waves.